Compatibility of legumes, an aromatic crop and a cereal as intercrops in palmarosa (Cymbopogon martinii Stapf.) - Singh, Munnu (Journal of Spices and Aromatic Crops, 2003)
To utilize the crop growth resources (space, time, water and nutrient) more efficiently during the initial stage, a field experiment was conducted during 1999-2000 in the semi-arid tropical climate of Bangalore, India to explore the feasibility of intercropping (food legumes, aromatic crop and cereal) in palmarosa. The intercropping combination palmarosa + basil resulted in the lnaximum (17%) increase in land use efficiency followed palmarosa + blackgram and palmarosa + soybean (16% each) and palmarosa + maize (5%). Palmarosa yield was not influenced by inter cropping system. Maximum net return was obtained with palmarosa + basil (Rs. 83635 ha-1) followed by palmarosa + blackgram (Rs. 83340 ha-1) and palmarosa + maize was the least remunerative inter cropping system (Rs. 68960 ha-1).